A Performance-Portable Kilometer-Scale Global Ocean Model on ORISE and New Sunway Heterogeneous Supercomputers - Wei, Junlin; Han, Xiang; Yu, Jiangfeng; Jiang, Jinrong; Liu, Hailong; Lin, Pengfei; Yu, Maoxue; Xu, Kai; Zhao, Lian; Wang, Pengfei; Zheng, Weipeng; Xie, Jingwei; et al. (SC24: International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
Ocean general circulation models (OGCMs) are indispensable for studying the multi-scale oceanic processes and climate change. High-resolution ocean simulations require immense computational power and thus become a challenge in climate science. We present LICOMK++, a performance-portable OGCM using Kokkos, to facilitate global kilometer-scale ocean simulations. The breakthroughs include: (1) we enhance cuttingedge Kokkos with the Sunway architecture, enabling LICOMK++ to become the first performance-portable OGCM on diversified architectures, i.e., Sunway processors, CUDA/HIP-based GPUs, and ARM CPUs. (2) LICOMK++ overcomes the one simulated-years-per-day (SYPD) performance challenge for global realistic OGCM at 1-km resolution. It records 1. 0 5 and 1.70 SYPD with a parallel efficiency of 54.8% and 55.6% scaling on almost the entire new Sunway supercomputer and two-thirds of the ORISE supercomputer. (3) LICOMK++ is the first global 1-km-resolution realistic OGCM to generate scientific results. It successfully reproduces mesoscale and submesoscale structures that have considerable climate effects.